The law and the lunatic - Sigerson, George (Statistical and Social Inquiry Society of Ireland, 1886)
Dr. Sigerson, having given an historical sketch of the subject, noted recent cases of abuse under the present system, and made a detailed analysis of the Lord Chancellor's Bill, proceeded as follows :? It must be borne in mind, however, that this project of an amended lunacy law must come up again for discussion de novo in the House of Lords, and be subject to the searching criticism of the House of Commons before it crystallizes into an Act of Parliament. With a view to the debates which must ensue, and the changes of form which it may have to undergo, I venture here to place on record certain points suggested by a careful analysis of the Bill, and by a studious examination of the lunacy laws of foreign countries.
Read Tuesday, 19th January, 1886
Keywords: Psychiatric health; Lunacy law; 314.15